Who owns desistance? A triad of agency enabling social structures in the desistance process - Albertson, Katherine (Theoretical criminology, 2022)
Theories of desistance assert agency is a prerequisite to the process; agency which can be enabled or curtailed by social structures. We present data from six community hub sites that hosted probation services in the UK in 2019. While our analysis identifies agency enabling institutional and relational structures across the different hub governance sub-types in our sample, these were clearest in hubs run in the community by the community. This article contributes a triad of core enabling social structures that operate at the intersection between agency and structure in the desistance process. The significance of our findings is that the ownership question is key to the expedition of enabling social structures.